2010
DOI: 10.1590/s1020-49892010000700003
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito vector abundance immediately before and after tropical storms Alma and Arthur, northern Belize, 2008

Abstract: Results indicated octenol is an effective attractant for An. crucians in northern Belize; malaria risk in Belize declines immediately post-storm (i.e., mosquito abundance drops); and arboviral risk associated with the rapid increase in culicine mosquitoes post-storm may represent a greater public health threat than malaria (although further research and active disease surveillance is necessary to validate this hypothesis).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…[32][33][34][35][36] Careful preparation for epidemics before the arrival of a cyclone is important to ensure a rapid response and control of outbreaks. Along with high death rates, the Philippines has experienced outbreaks of leptospirosis infection caused by coastal flooding after typhoons.…”
Section: Policy and Practicementioning
confidence: 99%
“…[32][33][34][35][36] Careful preparation for epidemics before the arrival of a cyclone is important to ensure a rapid response and control of outbreaks. Along with high death rates, the Philippines has experienced outbreaks of leptospirosis infection caused by coastal flooding after typhoons.…”
Section: Policy and Practicementioning
confidence: 99%
“…Although storm-related impacts on mosquito populations are well documented for floodwater nuisance species (Brown 1997, Simpson 2006, Breidenbaugh et al 2008, Morrow et al 2010, Lucas et al 2019, the impact on West Nile virus (WNV) vectors is less well known. Hurricane impacts on vector populations appear to be variable with respect to time since landfall and damage dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Barrera et al (2019) found that populations of the container-inhabiting mosquito, Aedes aegypti (L.), doubled following Hurricane Maria due to an increase in water-holding containers. Morrow et al (2010) documented an increase in Culex spp. mosquitoes immediately following tropical storms in Belize.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of different models of Mosquito Magnet ® (MM) (Woodstream Corporation, USA) for sampling mosquitoes has been compared with that of other collection methods, including that of human attraction. As a result, distinct models of MM have shown good performance for sampling mosquito populations under different environmental and climate conditions ( Pucci et al 2003 , Brown et al 2008 , Xue et al 2008 , Kitau et al 2010 , Morrow et al 2010 , Hiwat et al 2011a , Jawara et al 2011 , Missawa et al 2011, d , de Sá & Sallum 2013 ).…”
mentioning
confidence: 99%